Who Supports Climate Policies? Comprehensive Analyses in Finland and Beyond - Mustikkamaa, Sami (Westermarck-seura, 2025)
Kirja-arvio:
Arvosteltu teos: Jukka Sivonen: Public Attitudes on Climate Policy Instruments: A Comparative Perspective in Europe. Turku: University of Turku, 2023, 139 pp. ISBN 978-951-29-9416-8